(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
Strategies for coping with stress in children sheltered in social care institutions In this research are examined the strategies for coping with stress that are used by children sheltered in institutions for social protection. These children mostly used a strategy aimed at solving the problem (M = 66.6), and at least a strategy aimed at emotions (M = 34.6). This strategies are consisted of 15 possible ways of coping with stress so most children use emotional support (M —11.7), active coping (M = 11.6) and the use of social support (M - 11.5), and at least use of substances (M = 7.1), behavioural strategies (M = 9) and negation (M - 9.2).